Isolation and screening of indigenous strains of Haematococcus pluvialis Flotow for biomass and astaxanthin production - Xavier, Emanuel D. (2013)
International Symposium FloraMac2012. Colégio dos Jesuítas, Funchal, Madeira, 5-8 de Setembro.